Process-structural transformations as a vector for forming an innovative platform for modern construction development - Malyarenko , Oleksandr; Storozhuk , Oleksandr; Koshelnyi , Ivan; Buniak , Serhii; Rotov , Oleksandr (Ways to Improve Construction Efficiency, 2024)
The article examines process-structural transformations as a key vector for modernizing development activities in the context of digitalization, growing complexity of project environments, and evolving interaction models among market participants. The authors argue that the transition from fragmented management to integrated systems is a prerequisite for enhancing efficiency at all stages of a construction project’s life cycle. The focus is placed on new organizational models based on adaptability, partnership, and digital synergy. The study reviews recent research on economic and managerial evaluation of development, emphasizing the importance of implementing innovative tools to strengthen the market position of enterprises. The article provides an in-depth analysis of the evolution of economic and institutional approaches to forming a developer’s portfolio — from classic profit-oriented models to modern strategies that incorporate stakeholder, environmental, and regulatory considerations. A typology of business models for managing a development portfolio is presented, including platform-based, circular, digital, partnership, and service models. Their authorship, practical applications, and key performance indicators are identified. In the final section, the paper explores models for the targeted selection of performance indicators of construction enterprises, their etymological origins, methodological basis, and structural classification of diagnostic systems. The research findings can be applied in developing adaptive management models under conditions of environmental turbulence and growing demands for transparency and performance in the construction sector.